Adipose Extracellular Matrix/Stromal Vascular Fraction Gel: A Novel Adipose Tissue–Derived Injectable for Stem Cell Therapy. Issue 4 (April 2017) - Yao, Yao; Dong, Ziqing; Liao, Yunjun; Zhang, Pan; Ma, Jingjing; Gao, Jianhua; Lu, Feng
Abstract : Background: Adipose-derived stem cells and other stromal vascular fraction cells were used more often for stem cell therapy, even though limitations such as poor cell retention rate, complicated and expensive isolation processes, and the use of specific laboratory equipment need to be overcome. Methods: Here, the authors developed a novel but simple method for generating an injectable mixture of stromal vascular fraction cells and native adipose extracellular matrix. It is a purely mechanical process in which lipoaspirate is processed into an extracellular matrix/stromal vascular fraction gel. The standard processing procedure was established using quantized tests. The therapeutic potential of the product for wound healing was then tested. Results: Extracellular matrix/stromal vascular fraction gel derived from lipoaspirate and processed using a standard Coleman technique, followed by 1 minute of mechanical processing by passage back and forth between two 10-ml syringes at a flow rate of 10 ml/second, showed the highest adipose-derived stem cell and endothelial cell density. The stromal vascular fraction cells within the product also showed potential for multipotent differentiation similar to that of normal fat samples. In addition, the product showed better therapeutic results than stromal vascular fraction cell suspension when used to treat a nude mouse model of wound healing. Conclusions: Extracellular matrix/stromal vascular fraction gel is an autologous injectable derived from native extracellular matrix and is a functional cellular component generated using a simple mechanical process. As such, it may offer a novel mode of tissue repair suitable for clinical application in stem cell therapies. Abstract : Supplemental Digital Content is available in the text.